2018
DOI: 10.1038/natrevmats.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

Organic electrochemical transistors

Abstract: Organic electrochemical transistors (OECTs) leverage ion injection from an electrolyte into an organic semiconductor film to yield compelling advances in biological interfacing, printed logic circuitry and neuromorphic devices. Their defining characteristic is the coupling between electronic and ionic charges within the volume of an organic film. In this review we discuss the mechanism of operation and the 2 materials that are being used, overview the various form factors, fabrication technologies and proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
1,562
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 1,381 publications
(1,663 citation statements)
references
References 184 publications
14
1,562
0
9
Order By: Relevance
“…[42] As such, the state-retention times of electrochemical neuromorphic organic devices (ENODes) have thus far remained relatively short (<1 min). [46,47] Using the insights from this study, we confirm and mitigate the underlying degradation mechanisms by device encapsulation to demonstrate an order of magnitude improvement in ENODe state retention (from <1 min to ≈10 min), reduce cycling instability to <0.15%, and achieve long-term device stability of >30 days.…”
Section: Introductionmentioning
confidence: 59%
“…[42] As such, the state-retention times of electrochemical neuromorphic organic devices (ENODes) have thus far remained relatively short (<1 min). [46,47] Using the insights from this study, we confirm and mitigate the underlying degradation mechanisms by device encapsulation to demonstrate an order of magnitude improvement in ENODe state retention (from <1 min to ≈10 min), reduce cycling instability to <0.15%, and achieve long-term device stability of >30 days.…”
Section: Introductionmentioning
confidence: 59%
“…Grau et al demonstrated roll-to-roll printing of polymer TFTs on kaolin-coated packaging paper. One possibility to reduce the operating voltage of organic TFTs and circuits is the use of electrolyte-gated or electrochemical TFTs, [7,10,21] while electrolyte-gated and electrochemical TFTs can provide very large transconductances at very low operating voltages, [22] they usually suffer from large signal delays, as they involve the inherently slow movement of ions. One possibility to reduce the operating voltage of organic TFTs and circuits is the use of electrolyte-gated or electrochemical TFTs, [7,10,21] while electrolyte-gated and electrochemical TFTs can provide very large transconductances at very low operating voltages, [22] they usually suffer from large signal delays, as they involve the inherently slow movement of ions.…”
Section: Doi: 101002/aelm201800453mentioning
confidence: 99%
“…OECTs are three‐terminal devices in which a conjugated polymer thin‐film channel is patterned between two metal electrodes (drain and source) ( Figure a). The channel is in contact with an electrolyte in which an electrode (gate) is immersed . A voltage in the gate ( V G ) controls the doping state of the channel material, while the conductance of the channel is probed by measuring the drain current ( I D ) when applying a bias between the drain and source ( V D ).…”
Section: Introductionmentioning
confidence: 99%